Antioxidant and Antiapoptotic effect of aqueous extract of Pueraria tuberosa (Roxb. Ex Willd.) DC. On streptozotocin-induced diabetic nephropathy in rats - Rashmi Shukla; Somanshu Banerjee; Yamini B. Tripathi (BMC, 2018)
Abstract Background Oxidative stress and renal apoptosis play a significant role in the progression of diabetic nephropathy. The tubers of Pueraria tuberosa (Roxb. ex Willd.) DC. has been traditionally used as anti-ageing and health promotive tonic. The purpose of this study was to investigate its nephroprotective effect and mechanism via antioxidant and antiapoptotic potential in Streptozotocin-induced diabetic nephropathy (DN) in rats. Methods The chemical composition of aqueous extract of Pueraria tuberosa (PTY-2r) was analyzed by gas chromatography-mass spectrometry (GC-MS). Diabetes was induced by intraperitoneal injection of streptozotocin (STZ) (55 mg/kg body weight) in rats. After 60 days, the rats were randomly divided into 3 groups (n = 6/each group), namely DN control (DN) group-2, DN rats treated with PTY-2r at the dose of 50 mg/100 g, group-3 and 100 mg/100 g, group-4 p.o. for 20 days. The normal rats were chosen as a normal control (NC) group-1. PTY-2r was orally given to the rats for 20 days. Reactive oxygen species (ROS), lipid peroxidation (LPO) and the activity of ROS-scavenging enzymes - superoxide dismutase (SOD), catalase (CAT) & glutathione peroxidase (GPx) were determined in the kidney tissue of DN rats. The expression of apoptosis-related proteins was measured by immunofluorescence. Results GC-MS analysis of PTY-2r indicated the presence of 37 compounds among them 5-Hydroxymethylfurfural (17.80%), 2,3-dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one (17.03%), n-Hexadecanoic acid (5.18%) and 9-Octadecenoic acid (Z) - (6.69%) were found in the higher amount. A significant increase in ROS and LPO was observed along with the decreased activity of antioxidant enzymes, responsible for oxidative stress in the kidney of DN rats. Since, high oxidative stress induces apoptosis in target cells, as shown by significantly decreased expression of Bcl-2 along with increased expression of Bax, active Caspase-3 & cleaved PARP-1 in DN control rats, suggesting apoptosis. The PTY-2r treatment significantly raised the activity of antioxidant enzymes, suppressed oxidative stress and apoptosis thus, prevented urinary albumin excretion in a dose-dependent manner. Conclusions The findings suggest that PTY-2r exerted the nephroprotective potential against STZ induced DN rats via suppressing oxidative stress and apoptosis due to the presence of different bioactive compounds. Graphical Abstract ᅟ